СПЕЦИФИКА ЖАРГОННОЙ ЛЕКСИКИ - Джуманова, Д.Р. (SCIENCE and SOCIETY, 2021)
This article discusses the nature of jargons as a socially limited vocabulary, analyzes the factors of their appearance in speech, provides specific examples. Slang vocabulary includes the words and expressions of people who are united by a common profession, study, and common interests. In the language, there is a constant interpenetration of words from one group to another. The existing mobility of the boundaries between the vocabulary of the general people and vocabulary with a limited scope of use testifies to the continuous development and change of vocabulary.
Keywords: jargon; jargotism; argo; slang; socially restricted vocabulary; common words; colloquial speech